Antimalarial Activity of Artefenomel Against Asexual Parasites and Transmissible Gametocytes During Experimental Blood-Stage Plasmodium vivax Infection. (1st June 2020) - Collins, Katharine A; Abd-Rahman, Azrin N; Marquart, Louise; Ballard, Emma; Gobeau, Nathalie; Griffin, Paul; Chalon, Stephan; Möhrle, Jörg J; McCarthy, James S
Abstract: Background: Interventions that effectively target Plasmodium vivax are critical for the future control and elimination of malaria. We conducted a P. vi v ax volunteer infection study to characterize the antimalarial activity of artefenomel, a new drug candidate. Methods: Eight healthy, malaria-naive participants were intravenously inoculated with blood-stage P. vivax and subsequently received a single oral 200-mg dose of artefenomel. Blood samples were collected to monitor the development and clearance of parasitemia, and plasma artefenomel concentration. Mosquito feeding assays were conducted before artefenomel dosing to investigate parasite transmissibility. Results: Initial parasite clearance occurred in all participants after artefenomel administration (log10 parasite reduction ratio over 48 hours, 1.67; parasite clearance half-life, 8.67 hours). Recrudescence occurred in 7 participants 11–14 days after dosing. A minimum inhibitory concentration of 0.62 ng/mL and minimum parasiticidal concentration that achieves 90% of maximum effect of 0.83 ng/mL were estimated, and a single 300-mg dose was predicted to clear 10 9 parasites per milliliter with 95% certainty. Gametocytemia developed in all participants and was cleared 4–8 days after dosing. At peak gametocytemia, 75% of participants were infectious to mosquitoes. Conclusions: The in vivo antimalarial activity of artefenomel supports its further clinical development as a treatment for P. vivax malaria. Clinical Trials Registration: NCT02573857.